O "Grupo dos Onze": repressão e anticomunismo no município de Muniz Freire-ES - Caçador, Herbert Soares (2017)
The Brazilian political scene was marked by political instability. This environment was centered in the coup of 1964. The present work analyzes the formation process of the Group of Eleven in the municipality of Muniz Freire - ES and the consequences of its creation, such as: political and social repression and its connection to communism. It relies on a series of documents, especially the Military Police Inquiry (IPM), which resulted in the conviction and prison of nine of the eleven members of the group in 1966, as well as documents produced by the Police station of Order and Social Policy of the State of Espírito Santo (DOPS -ES), amnesty cases, various newspapers and minutes of Town Hall of Muniz Freire. It is also used from oral sources, with interviews of members of the group and other characters that were part of the local conjuncture in the 1960s. The work traces a panorama of the political history of the municipality based on the research, focusing on its origins, the characteristics of society, as well as the fierce political context in the locality. He studies the political trajectory of Leonel Brizola, then federal deputy for the Brazilian Labor Party (PTB) and creator of the Group of Eleven in a period in which the country was going through a serious political, economic and institutional crisis. It deals with party formation in Espírito Santo after the Estado Novo and the electoral contest in the municipality of Muniz Freire from 1945, focusing on the rise of the municipal PTB, a party that would leave some members of the Group of Eleven Muniz Freire. The final part of the paper approaches the trajectory of the members of the group and tries to understand how the creation of the Group of Eleven potentiated anticommunism in the municipality of Muniz Freire and stimulated vows of praise to the military that took power in 1964. The work also addresses the repression and persecution that marked the trajectory of some former participants of the Group of Eleven Muniz Freire.